2013
DOI: 10.3176/earth.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of surface sediment phosphorus fractions and water phosphorus concentration in Lake Peipsi (Estonia/Russia)

Abstract: Spatial and temporal variations in the contents of total phosphorus and five P-fractions were investigated in the surface sediments of large and shallow Lake Peipsi (area 3555 km2, mean depth 7.1 m) and compared with total phosphorus (TP), dissolved inorganic P (PO4-P) and dissolved oxygen (O2) concentration in the overlying water column. The aim of the study was to determine the relationships between the sediment P and water P concentration dynamics. Samples from the uppermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The lake is eutrophic with a mean total phosphorus concentration of 40 mg P m −3 and a total nitrogen concentration of 658 mg N m −3 in the ice-free period (Kangur and Möls, 2008). The existing limnological time-series data indicate that a deterioration of lake water quality has occurred (Kangur et al, 2009(Kangur et al, , 2013b.…”
Section: Study Sitementioning
confidence: 97%
“…The lake is eutrophic with a mean total phosphorus concentration of 40 mg P m −3 and a total nitrogen concentration of 658 mg N m −3 in the ice-free period (Kangur and Möls, 2008). The existing limnological time-series data indicate that a deterioration of lake water quality has occurred (Kangur et al, 2009(Kangur et al, , 2013b.…”
Section: Study Sitementioning
confidence: 97%
“…Moreover, Kangur, et al [18] and Zhang, et al [43] also reported that increased temperatures increase microbial processes and diffusion from the sediments resulting in elevated phosphorus concentration in the overlying water column. Furthermore, Søndergaard [42] explained that the increased temperature augments the rate of chemical diffusion and chemical processes, but the most significant impact on nutrient release is often via biological processes.…”
Section: Seasonal Variations Of Composite Sediment Nutrient Analyses mentioning
confidence: 99%
“…The results of the study for the spatial and temporal values of NO3-N, NO2-N, SRP, TP and TN concentrations and loads in the lake sediment samples in both composite and depth profiles are presented below: Sobczyński and Joniak [4] and Kangur, et al [18]. The main reason for the declining of SRP along depths of the sediment might be the 'bound up' of SRP with other metal complexes and not being actively released to the overlying water column.…”
Section: Spatial and Seasonal Trends In Nutrients Analysis In The Sedmentioning
confidence: 99%
“…A seasonal thermal stratification in deep lakes brings about vertical variation in phytoplankton composition [15,16]. In shallow water bodies, stratification is rarely observed [17], thus constant mixing of water column favour nutrient release from sediments [18]. Physico-chemical variables of lake water are the key components of water quality criteria for various uses, thus providing good indications of stressors in lake ecosystems [19].…”
Section: Introductionmentioning
confidence: 99%